2022
DOI: 10.1159/000525955
|View full text |Cite
|
Sign up to set email alerts
|

Novel Advances in the Study of IgG4-Related Disease in the Eye and Ocular Adnexa

Abstract: Immunoglobin (IgG4)-related disease in the eye and ocular adnexa (IgG4-ROD) is a newly discovered autoimmune disease that histologically exhibits extensive lymphocyte and plasma cell infiltration, occlusive phlebitis and mat or whorled fibrosis. The disease can affect multiple ocular tissues and organs, such as the lacrimal gland, extraocular muscles, orbital fat and trigeminal nerve. The main clinical manifestations are chronic, painless swelling of the orbit or unilateral orbit and proptosis, which may be ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Current treatments for IgG4-ROD are limited; therefore, it is essential to find an effective way to prevent lacrimal gland fibrosis and preserve lacrimal gland function. Some studies [11] found that the expression of extracellular matrix protein Fibulin-5 was significantly higher in IgG4-ROD lacrimal gland than in normal human lacrimal gland tissues, and it was speculated that Fibulin-5 protein was involved in the fibrosis of the lacrimal gland. RNAi technology can effectively silence the target gene so that the expression of related proteins decreases, which has been tested in mammalian cells; it can effectively inhibit the growth of viruses and tumor cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Current treatments for IgG4-ROD are limited; therefore, it is essential to find an effective way to prevent lacrimal gland fibrosis and preserve lacrimal gland function. Some studies [11] found that the expression of extracellular matrix protein Fibulin-5 was significantly higher in IgG4-ROD lacrimal gland than in normal human lacrimal gland tissues, and it was speculated that Fibulin-5 protein was involved in the fibrosis of the lacrimal gland. RNAi technology can effectively silence the target gene so that the expression of related proteins decreases, which has been tested in mammalian cells; it can effectively inhibit the growth of viruses and tumor cells [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…According to these criteria, the expression level of IgG4 is still the main reference index for diagnosis of this disease [ 14 , 15 ]. However, since there is evidence that IgG4 is positively expressed in a variety of diseases, elevated serum IgG4 is not considered specific to LGBLEL [ 16 ]. To improve the sensitivity of diagnosis and differentiation, Detiger et al have proposed the use of additional IHC staining of IgG2 + plasma cells and the histological IgG2/IgG4 ratio in diagnosis of IgG4-ROD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we report a rare case of LC with IgG4-RD. However, it is worth noting that IgG4-RD can involve any organ of the body, most commonly the pancreas, followed by the parotid gland, bile ducts, liver, lung, and lymph nodes [3]. Binocular conjunctival lesions can occur, but no evidence of IgG4-RD involvement has been found in other parts of the eye or other organs of the body.…”
Section: Discussionmentioning
confidence: 99%